2012
DOI: 10.1016/j.jbiotec.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermic temperatures on production of rabies virus glycoprotein by recombinant Drosophila melanogaster S2 cells cultured in suspension

Abstract: Aiming at maximizing the production of transmembrane rabies virus glycoprotein (rRVGP), the influence of hypothermic temperature on a recombinant Drosophila melanogaster S2 cell culture in Sf-900II medium was investigated. Cell growth and rRVGP production were assessed at 4 culture temperatures in Schott flasks: 16, 20, 24 and 28 °C. The maximum specific growth rates μ(max) were, respectively: 0.009, 0.019, 0.038 and 0.035 h(-1), while the maximum rRVGP levels C(max)(rRVGP) were: 0.075, 2.973, 0.480 and 1.404 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
3
11
1
Order By: Relevance
“…The maximum volumetric yield for RVGP (cell cultures plates with agitation) observed in the present work was lower than those reported for the same protein using stably transfected Drosophila melanogaster cells (1.5-3 mg L) with optimized culture conditions in bioreactors (Ventini et al 2010;Rossi et al 2012). Homogenization and aeration improvements could increase the RVGP expression.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The maximum volumetric yield for RVGP (cell cultures plates with agitation) observed in the present work was lower than those reported for the same protein using stably transfected Drosophila melanogaster cells (1.5-3 mg L) with optimized culture conditions in bioreactors (Ventini et al 2010;Rossi et al 2012). Homogenization and aeration improvements could increase the RVGP expression.…”
Section: Discussioncontrasting
confidence: 71%
“…At present, volumetric yield in spinner flask for RVGP are inferior to values of this parameter for the same heterologous protein and other proteins expressed with SFV vector in bioreactors (Blasey et al 2000;Ventini et al 2010;Rossi et al 2012). The diminution of time for maximum protein expression peak is another evidence of improved conditions for infection in spinner flask when compared with cell culture plate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Insights gained through detailed studies of S2 processes have led to a 9.3-fold increase in RVGP yield by lowering the production temperature to 22°C compared with the initial process conducted at 28°C [90]. Following this study, a detailed ana lysis of the effect of culture temperature on RVGP production between 16 and 28°C demonstrated that the best production was attained at 20°C while feeding limiting amino acids, as suggested by the study of Swiech et al [91]. An interesting 60% increase in RVGP production was seen for the addition of Lonomia oblique hemolymph [92]; it was shown that the positive effect was mainly early in the culture and was related to an increased maximum specific productivity of 60 ng/cell/day ver- Taken from [97].…”
Section: S2 Cells In Bioproductionmentioning
confidence: 54%
“…, 2013; Rossi et al . , 2012). Historically, CHO cells allowed gene amplification, resulting in a higher recombinant protein yield (up to the gram per liter range for some proteins) and specific productivity, which was previously an issue in other mammalian cell lines (Carlage et al .…”
Section: Introductionmentioning
confidence: 99%